Energy-environmental evaluation of conventional and variable rate technology sprayer; application of Life Cycle Assessment - Rostam Fathi; Mahmoud Ghasemi-Nejad-Raeini; Saman Abdanan Mehdizadeh; Morteza Taki; Mostafa Mardani Najafabadi (PLoS ONE, 2025)
The objective of this research was to conduct a comprehensive evaluation of the energy and environmental efficiency of a smart sprayer with a variable rate in orange production. The smart sprayer was developed from a standard orchard sprayer with a fixed rate using different equipment. Energy indicators, encompassing energy efficiency, energy productivity, energy intensity and net energy gain, were calculated. Environmental indicators, including global warming potential, acidification, eutrophication and human toxicity potentials, were estimated using the Life Cycle Assessment (LCA) method in 15 midpoint and 4 endpoint categories. The findings demonstrated that the smart sprayer with a variable rate held a significant advantage over the conventional sprayer with a fixed rate in terms of reducing the pesticide deposition on the trees, lowering pesticide consumption, increasing the energy efficiency and productivity and mitigating the environmental impacts. The maximum pesticide lowering was 46%, achieved at a speed of 1.6 km.hr-1. The energy efficiency and productivity changed from 0.594 to 0.650 and from 0.313 to 0.342 kg.MJ-1, respectively. The Global Warming Potential (GWP) declined from 422.860 to 407.573 kg CO2 eq per ton of orange production. The reduction of chemical pesticide, diesel fuel and agricultural machinery consumption contributed to the decrease in environmental emissions. Consequently, the smart sprayer with a variable rate emerged as a significantly more sustainable and efficient solution for orange production.